Diagnóstico del sistema de alcantarillado pluvial del tramo de ruta nacional 228 en Cartago - Carmona-Jiménez, Jean Poll (Instituto Tecnológico de Costa Rica, 2014)
The next project is to pose a diagnostic storm sewer. Areas of study covered correspond to the topography, hydrology and hydraulics. It was necessary, the use of computer programs, information gathering field literature on the estimation of flow, hydraulic design and periodic maintenance plan. The aim is to reduce flooding problems that occur around the path, through a diagnosis including some proposed stormwater points vent, which discharge flow saturating the current sewer system with a respective plan periodic maintenance. Bibliographic reference materials, computer software, field measurement tools was used and the scientific method was applied. The result of this project, is a diagnosis of the sewer system with a configuration of points vent, to download the current pipeline system, which includes a new storm sewer design to reduce flooding in the rainy season and a maintenance plan newspaper. It is concluded that the current storm sewer system in the area, has the right to meet the demands of flow conditions. As this proposal seeks to reduce flooding problems generated in the stretch
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Diseño hidráulico; Desfogue pluvial; Análisis hidrológico; Tuberías; Mantenimiento; Diagnóstico